Stasis, Fragmentation, and Change: An Empirical Analysis of Police Reform in Jamaica (2000 - 2021) - Anderson, Jody-Ann (Université d'Ottawa | University of Ottawa, 2025)
The murder of an African American man, George Floyd, by a white police officer on May 25, 2020, in Minnesota, United States of America, ignited a wave of social movements and public outcry against police brutality globally. This increased focus on police violence and its connection to intersecting social hierarchies contributed to the resurgence of debates about this issue’s pervasiveness elsewhere, notably middle-income developing countries (MICs) in Latin America and the Caribbean (LAC) – contexts with some of the highest levels of homicides globally. Yet historically, efforts to reform police institutions and their practices have been disappointing despite significant financial investments. To remedy gaps in reform thinking and implementation, scholars have proposed various factors that they consider critical missing links, including research on implemented reform efforts may have underestimated or overlooked reform gains and the conditions that facilitated more promising outcomes. In response to these arguments, and with an optimism that sustainable institutional change is possible, this thesis uses Jamaica as a case study of police reform in a specific MIC in LAC. Using a broadened institutionalist theoretical lens and grounded in comparative case study methods, it focuses on the Jamaica Constabulary Force’s (JCF) reform outcomes, particularly about the use of force and factors influencing change in these outcomes. The thesis is structured across four different but related articles. Specifically, articles one to three home in on the use of force and explore changes in the JCF at different levels of analysis: regional (Americas), national, and divisional. Article four complements the first three in its focus on change, but it adds depth by homing in on the conditions influencing change in the JCF. Combined, they offer a cohesive analysis of the JCF’s use of force and the conditions contributing to police reform. The collection of articles in this thesis makes several original contributions to the literature and discourse on security sector reform, particularly regarding policing and police reform in Jamaica and comparable contexts. Specifically, it makes a methodological argument for how police reform should be studied, theorises how change can be more consistently categorised, localises police reform at both the national and divisional/community levels, and re-emphasises the reform-crime interconnections.
Keywords: Police reform; Policing; Institutional Change; Jamaica Constabulary Force; RCMP